Measuring maternal body composition by biomedical impedance can predict risk for gestational diabetes mellitus: a retrospective study among 22, 223 women. (18th July 2022) - Zhang, Rui-Yuan; Wang, Lan; Zhou, Wei; Zhong, Qi-Mei; Tong, Chao; Zhang, Ting; Han, Ting-Li; Wang, Lian-Rong; Fan, Xin; Zhao, Yan; Ran, Rui-Tu; Xia, Yin-Yin; et al.
Abstract: Objectives: This study aimed to identify which element of body composition measurements taken before 17th week gestation was the strongest risk factor for gestational diabetes mellitus (GDM) in Chinese pregnant women. Design and setting: A retrospective study was performed using data retrieved from the Electronic Medical Record database of Chongqing Health Center for Women and Children (China) from January 2014 to December 2015. Participants: A total of 22, 223 women were included with singleton pregnancies and no preexisting diabetes who underwent bioelectrical impedance analysis (BIA) before 17 gestational weeks and 75-g OGTT at 24–28 gestational weeks. Results: The prevalence of GDM from 2014 to 2015 was 27.13% (IADPSG). All indicators of BIA (total body water, fat mass, fat-free mass, percent body fat, muscle mass, visceral fat levels, proteins, bone minerals, basal metabolic rate, lean trunk mass), age, weight and body mass index (BMI) were risk factors that significantly increased the occurrence of GDM ( p  < .001 for all). Women older than 30 years or with a BMI more than 23, had a significantly higher GDM prevalence (34.89% and 34.77%). After adjusted covariates, visceral fat levels at the third quartile, the ORs of GDM were 1.142 (95% CI 1.032–1.263) in model I and 1.419 (95% CI 1.274–1.581) in model II used the first quartile as reference ( p  < .05 for both); bone minerals at the third quartile, the ORs of GDM were 1.124 (95% CI 1.020–1.238) in model I and 1.311 (95% CI 1.192–1.442) in model II ( p  < .05 for both). After adjusted for age, visceral fat levels and bone minerals, OR of GDM for percent body fat more than 28.77% at the third quartile was 1.334 (95% CI 1.201–1.482) in model II ( p  < .05 for both). Conclusions: Visceral fat levels, bone minerals and percent body fat were significantly associated with an increased risk of GDM, providing the reference ranges of visceral fat levels, bone minerals and percent body fat as predictive factors for Chinese women to estimate the risk of GDM by BIA during pregnancy.